POTENSI PEMANFAATAN LIMBAH ORGANIK RUMAH TANGGA MENJADI PUPUK ORGANIK CAIR MELALUI PROSES FERMENTASI MENGGUNAKAN BIOAKTIVATOR EM4 - Hendro Jatmiko Sormin; Daniel Daniel; Nataniel Tandirogang (JURNAL KIMIA MULAWARMAN, 2025)
Desa Girimukti is a village of East Kalimantan, Penajam Paser Utara. According to data for 2021, a privately owned area of around 16,000 ha will have a population of 6,730 persons and 1,908 occupied homes. The rising creation of garbage, especially home organic waste, is being caused by a sizable population. If handled improperly, it will contaminate the environment. Utilizing fermentation to transform trash into liquid organic fertilizer is one solution that is possible. Study In order to produce liquid organic fertilizer, it is necessary to know the ideal ratio of organic waste to bioactivator as well as the best fermentation time to obtain the highest nutritional content. In this research, EM4, water, and sugar are added to a reactor that already has household organic waste present in the form of vegetables. In order to test the macronutrient content, which includes C-organic, N, P, K, and pH, samples were taken on days 5, 10, and 15 of the 15-day fermentation process. In this study, the addition ratio of EM4 to vegetable waste was 30:100, with a lengthy fermentation period of 10 days. This provided the finest liquid organic fertilizer. The best pH, C-organic content, N, P, and K contents are 11.99%, 4.45%, 5.54%, 4.8200%, and 6.82, respectively. The produced liquid organic fertilizer satisfies the requirements for quality of MOA 70 of 2011.